Joint replacement rehabilitation and the role of funding source - Deborah L. Snell; Jennifer A. Dunn; K. Anne Sinnott; C. Jean Hsieh; Gerben De Jong; Gary J. Hooper (Medical Journals Sweden, 2019)
Objective: To examine associations between funding source, use of rehabilitation and outcomes after total joint replacement and to evaluate variations based on demographic characteristics. Design: Cross-sectional, questionnaire-based national survey. Subjects: Participants aged 45 years or older (n = 522) who received either private or public funding for their surgery, were recruited from the New Zealand Joint Registry 6 months after a total hip, total knee or unicompartmental knee replacement. Results: The cohort was predominantly New Zealand European (90%), aged 68 years, with more men (55%) than women (45%). Privately funded participants were younger, had higher levels of education and employment, and lower rates of comorbidities at the time of surgery. Privately funded participants also reported spending less time on the surgical waiting list, were less likely to participate in pre-surgical rehabilitation, but reported more weeks of post-surgical rehabilitation and better patient-reported outcomes in terms of pain, function and quality of life, compared with their publicly funded counterparts. Conclusion: Factors already known to impact on joint replacement outcomes were associated with funding source in this cohort. Socio-economic differences and inequities between private and public systems exist consistent with limited available prior research. In this cross-sectional study, no clinically significant differences in outcomes between the groups were identified. Prospective research will help to clarify whether funding source directly affects joint replacement rehabilitation outcomes.